If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 + 8k = -52 Solving -12 + 8k = -52 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 8k = -52 + 12 Combine like terms: -12 + 12 = 0 0 + 8k = -52 + 12 8k = -52 + 12 Combine like terms: -52 + 12 = -40 8k = -40 Divide each side by '8'. k = -5 Simplifying k = -5
| y+3x=180 | | 3x(4*25)=250 | | 50=-3x-2(x-10) | | 3x(4*25)=541 | | 7x-7(5x-1)=7 | | 180+9x=4x-40 | | 4x+12=4x+10 | | (x-8)(4x-3)=0 | | -15=4-3(-3.6) | | -6+5x=36 | | (x+6)(4x-3)=0 | | -2x+6=2x-30 | | 8r+4(r-7)=-2(3r+10) | | 5-8y+11y=-13+3 | | -4(x+1)=-2(8-x) | | (x+6)(x-8)=0 | | -55+6x+3x=3132 | | 12=8 | | (x+6)(x-8)(4x-3)=0 | | 6x+8=-4x+8 | | -3x+7=-14-6x | | y=80x+900 | | 188=-2+4(6x-8) | | -3x+3=2x-12 | | 6(4x+5)=2x | | -1+6x=17 | | 14x-2x^2=x | | 3m+3=m-5 | | 13x-7x+5x=-11 | | 8=4(3c+3) | | -10v=60 | | 2t-2=-2 |